Grape seed extract ameliorates bleomycin-induced mouse pulmonary fibrosis. (5th May 2017) - Liu, Qi; Jiang, Jun-xia; Liu, Ya-nan; Ge, Ling-tian; Guan, Yan; Zhao, Wei; Jia, Yong-liang; Dong, Xin-wei; Sun, Yun; Xie, Qiang-min
Highlights: Bleomycin induces pulmonary fibrosis in mice. Grape seed extract (GSE) reduces cytokines and inflammatory cell infiltration. GSE ameliorates TGF-β and MMP-9 expression. GSE inhibits lung fibrotic markers and improves pulmonary function. GSE prevents bleomycin-induced pulmonary fibrosis in mice through its anti-inflammatory and anti-fibrotic effects. Abstract: Pulmonary fibrosis is common in a variety of inflammatory lung diseases, such as interstitial pneumonia, chronic obstructive pulmonary disease, and silicosis. There is currently no effective clinical drug treatment. It has been reported that grape seed extracts (GSE) has extensive pharmacological effects with minimal toxicity. Although it has been found that GSE can improve the lung collagen deposition and fibrosis pathology induced by bleomycin in rat, its effects on pulmonary function, inflammation, growth factors, matrix metalloproteinases and epithelial-mesenchymal transition remain to be researched. In the present study, we studied whether GSE provided protection against bleomycin (BLM)-induced mouse pulmonary fibrosis. ICR strain mice were treated with BLM in order to establish pulmonary fibrosis models. GSE was given daily via intragastric administration for three weeks starting at one day after intratracheal instillation. GSE at 50 or 100 mg/kg significantly reduced BLM-induced inflammatory cells infiltration, proinflammatory factor protein expression, and hydroxyproline in lung tissues, and improved pulmonary function in mice. Additionally, treatment with GSE also significantly impaired BLM-induced increases in lung fibrotic marker expression (collagen type I alpha 1 and fibronectin 1) and decreases in an anti-fibrotic marker (E-cadherin). Further investigation indicated that the possible molecular targets of GSE are matrix metalloproteinases-9 (MMP-9) and TGF-β1, given that treatment with GSE significantly prevented BLM-induced increases in MMP-9 and TGF-β1 expression in the lungs. Together, these results suggest that supplementation with GSE may improve the quality of life of lung fibrosis patients by inhibiting MMP-9 and TGF-β1 expression in the lungs.